Photoluminescence and raman scattering of GaAs1-xBix alloy - L. Hasanah,; Julian, C.; Mulyanti, B.; Aransa, A.; Sumatri, R.; M.H. Johari,; David, J.P.R.; Abdul Rahman Mohmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Photoluminescence (PL) and Raman spectra of GaAs1-xBix samples grown at different rates (0.09 to 0.5 µm/h) were investigated. The PL peak wavelength initially redshifted with the increase of growth rate and reached the longest wavelength (1158 nm) for sample grown at 0.23 µm/h. This is followed by PL peak wavelength blueshift for higher growth rates. The Raman data show peaks at 162, 228, 270, and 295 cm-1 which can be attributed to GaAs like phonons. GaBi like vibrational modes were also observed at 183 and 213 cm-1. However, the intensity of Bi induced phonons is significantly weaker compared to GaAs due to low concentration of Bi compared to As and thin GaAs1-xBix epilayer. The PL data and GaAs transverse optical (TO) to longitudinal optical (LO) phonons intensity ratio indicate that Bi concentration is highly dependent on the growth rate and the highest Bi concentration was obtained by sample grown at 0.23 µm/h. It is found that the full-width-at-half-maximum (FWHM) of GaAs LO mode increases significantly for samples grown at high growth rates suggesting crystal quality degradation due to lack of surfactant effects.